Direct analysis of δ(2)H and δ(18)O in natural and enriched human urine using laser-based, Off-Axis Integrated Cavity Output Spectroscopy - Berman, Elena S.F. (2012)
The stable isotopes of hydrogen (δ(2)H) and oxygen (δ(18)O) in human urine are measured during studies of total energy expenditure by the doubly labeled water method, measurement of total body water, and measurement of insulin resistance by glucose disposal among other applications. An ultrasensitive laser absorption spectrometer based on off-axis integrated cavity output spectroscopy was demonstrated for simple and inexpensive measurement of stable isotopes in natural isotopic abundance and isotopically enriched human urine. Preparation of urine for analysis was simple and rapid (approx. 25 samples per hour), requiring no decolorizing or distillation steps. Analysis schemes were demonstrated to address sample-to-sample memory while still allowing analysis of 45 natural or 30 enriched urine samples per day. The instrument was linear over a wide range of water isotopes (δ(2)H = −454 to +1702 ‰ and δ(18)O= −58.3 to +265 ‰). Measurements of human urine were precise to better than 0.65 ‰ 1σ for δ(2)H and 0.09 ‰ 1σ for δ(18)O for natural urines, 1.1 ‰ 1σ for δ(2)H and 0.13 ‰ 1σ for δ(18)O for low enriched urines, and 1.0 ‰ 1σ for δ(2)H and 0.08 ‰ 1σ for δ(18)O for high enriched urines. Furthermore, the accuracy of the isotope measurements of human urines was verified to better than ±0.81 ‰ in δ(2)H and ±0.13 ‰ in δ(18)O (average deviation) against three independent IRMS laboratories. The ability to immediately and inexpensively measure the stable isotopes of water in human urine is expected to increase the number and variety of experiments which can be undertaken.